Experimental investigation on convective condensation heat transfer in horizontal 4mm diameter coated tube. (February 2022) - Chen, Jingxiang; Li, Wei; Fu, Cheng; Xu, Dachuan
Highlights: A microporous coating layer of 0.2 mm was sintered in a 4-mm I.D. tube. Condensation heat transfer coefficient and pressure drop of coated tube was evaluated. Mass flux and vapor quality effects on condensation heat transfer coefficient were discussed. A significant enhancement of convective condensation performance in coated tube was found. Abstract: Convective flow condensation heat transfer coefficient and pressure drop characteristics inside a coated tube and an equivalent smooth tube with an inner diameter of 4 mm were conducted by using refrigerant R410A. A microporous surface coating layer of approximately 0.2-mm thickness was sintered in the inner surface of the test tube. All condensation runs in the two tested tubes were conducted at saturation temperature 40 ± 0.2 °C, a mass flux range from 307.3 kg/(m 2 s) to 998.5 kg/(m 2 s), and a vapor quality range from 0.2 to 0.9. The experimental results show that the micro surface coating layer produces 32.97% to 44.78% higher heat transfer coefficient than the smooth tube when vapor quality ranged from 0.9 to 0.2 along the test tube, and yielded a 21.3% overall thermal benefit compared with the smooth tube. For mass flux of 450 kg/(m 2 s), 650 kg/(m 2 s), and 875 kg/(m 2 s), the surface-coated tube produces 37.70% to 54.57%, 28.29% to 41.05%, and 24.9% to 51.39% higher benefits than that of the equivalent smooth tube, respectively. Experimental data indicate that the surface-coated tube presented better thermal performances at high mass flux and high vapor quality region. Ten available condensation heat transfer coefficient correlations for annular or stratified/annular flow were examined, and the prediction results show that correlations over predict condensation heat transfer coefficient of smooth tube and present a better prediction for the surface-coated tube.